Great apes use landmark cues over spatial relations to find hidden food - Hribar, Alenka; Call, Josep (Animal cognition, 2011)
We investigated whether chimpanzees, bonobos, and orangutans encoded the location of a reward hidden underneath one of three identical cups in relation to (1) the other cups in the array—i.e., the relative position of the baited cup within the array; or (2) the landmarks surrounding the cups—e.g., the edge of the table. Apes witnessed the hiding of a food reward under one of three cups forming a straight line on a platform. After 30 s, they were allowed to search for the reward. In three different experiments, we varied the distance of the cups to the edge of the platform and the distance between the cups. Results showed that both manipulated variables affected apes’ retrieval accuracy. Subjects’ retrieval accuracy was higher for the outer cups compared with the Middle cup, especially if the outer cups were located next to the platform’s edge. Additionally, the larger the distance between the cups, the better performance became.